Development of a Model-Based Approach to Capture Battery Parameter Degradation in Satellites. (25th November 2020) - Knap, Vaclav; Bęczkowski, Szymon Michal; Stroe, Daniel-Ioan
Abstract : There is an increasing number of CubeSats being launched on the Earth's orbit. They are typically based on commercial off-the-shelf batteries that are not primarily designed for space applications. Thus, their actual degradation in this environment needs to be considered, compared to on-ground laboratory conditions. In this work, a model-based method is introduced for tracking the change in battery model parameters, including the battery capacity. The method is based on collected telemetry data and it covers specific and variable battery temperature conditions in CubeSats. However, it is shown that the method is sensitive to telemetry quality, regarding sample resolution and sample loss. Thus, the used settings could not determine battery degradation trends with high confidence. Nevertheless, steps for improvement were identified that shall increase the accuracy of the results in future work.